Lottery-Based Payment Mechanism for Microtasks - Celis, L.; Roy, Shourya; Mishra, Vivek (Proceedings of the AAAI Conference on Human Computation and Crowdsourcing, 2013)
We propose using lotteries as an alternative payment mechanism through which to incentivize and recruit workers to microtasking. We present initial findings gained via experiments on Amazon Mechanical Turk and focus on discussing the benefits and potential pitfalls in employing a lottery-based payment mechanism for microtasking.